SISTEM INFORMASI LAPANGAN FUTSAL DENGAN ALGORTIMA ANTREAN (FCFS) BERBASIS WEBSITE - Mayadi, Mayadi; Rakhmi Khalida; Prio Kustanto; Andy Achmad Hendharsetiawan (Journal of Innovation Research and Knowledge, 2025)
As time goes by, the development of information systems is increasingly enhanced by the advancement of sophisticated technology. Information systems are based on human needs to store and process information more effectively and efficiently. Sports that are currently popular, such as futsal, have garnered significant interest. Futsal is a sport played by five players one achteam,withtheo bjective of scoring goals by manipulating theball. Thegrowing demand for futsal fields has led to the need for a booking and scheduling system, where customers orpotential futsal players must visitthe location inperson to makea booking, which consumes time and costs. Before making abooking, customers must first check the availability of the field on the desired day and time, a process that is still done manually by going to the venue. Online booking is the process of arranging reservations for products or services. It involve screating amethodo fordering (forplaces,goods,etc.)tootherswhilebeingconnected to the internet. Therefore, online booking can be defined as the reservation of products or services conducted through an internet connection. To maximize the online booking system, the First Come First Serve algorithm is required to aid in the effective creation of the online booking system. The First Come First Serve (FCFS) algorithm is the simplest scheduling algorithm used by CPUs. Hence, the author has chosen the title “Design of the JB Futsal Booking System Using the First Come First Served (FCFS) Algorithm.”